Investigation of grease lubricated deep groove ball bearing with multi-defected outer race using vibration signature analysis. (July 2021) - Utpat, Abhay A; Kulkarni, Sham; Ingle, Ravindra B
Failure of any rotary machine is mainly due to bearing failure being the key element. Defect frequency is the function of speed, ball diameter, and pitch circle diameter of bearing. The number of defects does not affect the excitation frequency, but increase in the level of vibrations is observed in total. The inner race is mounted on the rotary shaft, and the outer race is fixed in the housing. Hence, a defect on the outer race does not rotate with the shaft. This article highlights the study of the multi-crack detection technique at a comparatively higher speed. Amplitudes of vibrations increase with speed, but with load, they almost remain the same. The experiment has been performed at the range from 1000 to 5000 r/min with 5 kg load on the test bearing. The location and size of the defect affect the level of vibrations with noticeable increase. However, the presence of a second defect with respect to the load zone plays an important role. As the defect is at the peak position in the load zone, outer race defect frequency excites more in the vibration spectra. The location and size of the second defect are varied, and acceleration amplitude parameters like RMS, peak, and peak to peak are compared. The current work emphasizes the effect of location and severity of the second defect on the vibration spectra and amplitude parameters of the vibrations.